The fix (2016), volume 3 ebook - Spencer, Nick (The Fix (2016), 2018)
Roy makes a big breakthrough in his murder investigation, while Mac is out for justice. Collects THE FIX #9-12 Author: Nick Spencer. Illustrator: Steve Lieber. 2018 Nick Spencer/Steve Liebor